(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The aim of this paper is to describe the relationship between the competencies of employees and their performance in one particular company. Semi-structured interviews and analysis of internal documents of the company took place between 2010 and 2011 and led to the characterization of the competency and performance evaluation system. The tools of evaluation used by the company are described. The evaluation of competency and performance of 110 employees made by 22 evaluators is an input to quantitative research. Calculations include data on the evaluation of all employees who met the following conditions (1) the employment lasted throughout the test period from 2007 to 2009, employee’s performance was evaluated regularly in the given period, (3) employees’ competencies were assessed in 2007. Null hypothesis, which has not been accepted, says that there is no relationship between competency and employee’s performance. The results of the research suggest that when the competency rate of one employee is a unit higher than the competency rate of another employee, it can be assumed that his performance rate is 7 to 12.5 higher. Recommendations for improving of the evaluation system of the company, which can be used in any company where employees’ performance and competencies are evaluated, are formulated in the discussion.